Phenotypic characterization of regulatory T cells populations in maternal blood, cord blood and placenta from diabetic mothers - Queiroz, Adriele A.; França, Eduardo L.; Hara, Cristiane C. P.; Honorio, Mariana S.; Fagundes, Danny L. G.; Calderon, Iracema M. P.; Honorio-França, Adenilda C. (Taylor & Francis, 2017)
Purpose: Changes in regulatory T cells (Treg) in peripheral blood are associated with a number of pathologies, including diabetes. However, the immunological responses of pregnant diabetic women remain scarcely known, and the effects of Treg cells in these patients have yet to be investigated. The present study characterized the expression of regulatory T cells in the maternal blood, cord blood and placenta of diabetic pregnant women. Materials and methods: The women were divided according to glycemic status into a non-diabetic (ND; N = 20) or type 2 diabetic (T2DM; N = 20) group. Cell subsets were determined by flow cytometry. Results: Compared to ND, T2DM blood cells exhibited a higher expression of CD25+, Foxp3+, CD4+CD25+, CD4+Foxp3+ and CD25+Foxp3+; and cord blood cells showed a lower expression of CD25+, CD4+Foxp3+ and CD25+Foxp3+. In the placenta of T2DM, the villous layer of the proportion, CD3+ and CD25 was lower than that of CD4+Foxp3+ and CD25+Foxp3+, and the extravillous placenta layer contained the lowest levels of CD4+ and CD25+ and highest proportions of CD4+Foxp3+. In maternal blood from T2DM, the frequency of CD3+CD95+ and CD3CD4+ T cells expressing CD95+ was lower. In cord blood from T2DM, the rate of CD3+CD95+ was lower. The placenta villous layer of T2DM showed a lower count of CD3+CD95+ and of CD3CD4+ T cells expressing CD95+, whereas the number of cells expressing CD3+CD45RO+ decreased in both placental layers. Conclusion: The data obtained suggest that hyperglycemia changes the phenotypes of regulatory T cells and Fas expression in memory T cells.
Keywords: diabetes; Fas; placenta; pregnancy; Treg cells